Pengaruh Kompetensi SDM, Pemanfaatan Teknologi Informasi, dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Empiris pada Pemda Tanggamus) - Nabila Aurelia; Rosmiati Tarmizi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to investigate the impact of human resource competencies, use of information technology, and internal control systems on the quality of financial reporting in Tangamus District Municipality. The study uses a quantitative approach and applies a targeted sampling technique to her 35 respondents who are employees or financial managers in the accounting department. Data analysis was performed using the multiple linear regression method. The study results show that the use of human resource competencies, information technology and internal control systems have a positive and significant impact on the quality of financial reporting in Tangams District Municipality.